Ulcerative colitis. (May 2015) - Ho, Gwo-Tzer; Boyapati, Ray; Satsangi, Jack
Abstract Ulcerative colitis (UC) and Crohn's disease (CD) represent the two major forms of inflammatory bowel disease (IBD). UC is a chronic idiopathic inflammatory condition affecting the colon and rectum. A complex interplay between components of the innate immune system and environmental factors, notably the microflora, regulates colonic mucosal homeostasis, which is dysregulated in UC. In this chapter, we review current concepts of the epidemiology, pathogenesis, clinical features and management of UC.